2011
DOI: 10.1007/s10902-011-9249-7
|View full text |Cite
|
Sign up to set email alerts
|

Linking Peoples’ Pursuit of Eudaimonia and Hedonia with Characteristics of their Parents: Parenting Styles, Verbally Endorsed Values, and Role Modeling

Abstract: Research on eudaimonia (seeking to use and develop the best in oneself) and hedonia (seeking pleasure, enjoyment, comfort), two dominant ways of pursuing the good life, has previously focused on their well-being consequences and correlates. Little is known about their predictors. Two retrospective studies with undergraduates began investigating the links between the behavior of one's parents when one was a child, and the degree to which one pursues eudaimonia and/or hedonia and derives well-being from these pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…Eudaimonic approaches also emphasise that wellbeing and happiness are on-going processes, not end states. Despite this, like hedonia, eudaimonia has been considered at both the wellbeing and activity levels, with activities that are intrinsically motivated and afford development in oneself often emphasised as pathways to wellbeing (Huta, 2012). Hedonia and eudaimonia have, therefore, both been considered as ways of living/behaving, and more globally, as wellbeing types.…”
Section: From Philosophy To Sciencementioning
confidence: 99%
“…Eudaimonic approaches also emphasise that wellbeing and happiness are on-going processes, not end states. Despite this, like hedonia, eudaimonia has been considered at both the wellbeing and activity levels, with activities that are intrinsically motivated and afford development in oneself often emphasised as pathways to wellbeing (Huta, 2012). Hedonia and eudaimonia have, therefore, both been considered as ways of living/behaving, and more globally, as wellbeing types.…”
Section: From Philosophy To Sciencementioning
confidence: 99%
“…Recent research by Huta (2012) and Huta and Ryan (2012; suggested that people experience greater well-being when their pursuits of happiness include both hedonic and eudaimonic aspects of well-being. conducted four studies regarding these two aspects of well-being.…”
Section: New Contributions To the Understanding Of Happiness And Wellmentioning
confidence: 99%
“…This finding suggests the need for both orientations toward well-being, a balance of the two that supports greater wellbeing. Huta (2012) acknowledged limitations of the studies --they were retrospective and correlational rather than being longitudinal or providing causal data --but she suggested that since parents want what is best for their children, this research may begin to "clarify which strategies make a difference" in children's motivations for the pursuit of happiness and wellbeing (p. 59).…”
Section: New Contributions To the Understanding Of Happiness And Wellmentioning
confidence: 99%
“…At the activity or behaviour level, hedonic approaches mainly emphasise the importance of engaging in pursuits through which positive emotional experiences, like pleasure, enjoyment, comfort, can be gained, and that lead to satisfaction of individual's desires (Fredrickson 2001;Kahneman et al 1999). Eudaimonic approaches emphasise intrinsically motivated activities that provide opportunities for personal development as paths to well-being (Huta 2011).…”
mentioning
confidence: 99%